G-quadruplex-forming small RNA inhibits coronavirus and influenza A virus replication - Ryoya Sekine; Kouki Takeda; Tsukasa Suenaga; Satsuki Tsuno; Takumi Kaiya; Maki Kiso; Seiya Yamayoshi; Yoshihide Takaku; Shiho Ohno; Yoshiki Yamaguchi; Seiichi Nishizawa; Kazuhiro Sumitomo; et al. (Communications Biology)
Abstract Future pandemic threats may be caused by novel coronaviruses and influenza A viruses. Here we show that when directly added to a cell culture, 12mer guanine RNA (G12) and its phosphorothioate-linked derivatives (G12(S)), rapidly entered cytoplasm and suppressed the propagation of human coronaviruses and influenza A viruses to between 1/100 and nearly 1/1000 of normal virus infectivity without cellular toxicity and induction of innate immunity. Moreover, G12(S) alleviated the weight loss caused by coronavirus infection in mice. G12(S) might exhibit a stable G-tetrad with left-handed parallel-stranded G-quadruplex, and inhibit the replication process by impeding interaction between viral nucleoproteins and viral RNA in the cytoplasm. Unlike previous antiviral strategies that target the G-quadruplexes of the viral genome, we now show that excess exogenous G-quadruplex-forming small RNA displaces genomic RNA from ribonucleoprotein, effectively inhibiting viral replication. The approach has the potential to facilitate the creation of versatile middle-molecule antivirals featuring lipid nanoparticle-free delivery.